2015
DOI: 10.1186/s13071-015-0836-z
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the microbiota in the guts of Triatoma brasiliensis and Triatoma pseudomaculata infected by Trypanosoma cruzi in natural conditions using culture independent methods

Abstract: BackgroundChagas disease is caused by Trypanosoma cruzi, which is transmitted by triatomine vectors. The northeastern region of Brazil is endemic for Chagas disease and has the largest diversity of triatomine species. T. cruzi development in its triatomine vector depends on diverse factors, including the composition of bacterial gut microbiota.MethodsWe characterized the triatomines captured in the municipality of Russas (Ceará) by sequencing the cytochrome c oxidase subunit I (COI) gene. The composition of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
123
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(143 citation statements)
references
References 91 publications
11
123
2
2
Order By: Relevance
“…Some differences in the taxonomic composition of triatomine gut bacterial communities were found in our study, in comparison with previous results obtained with non-culture- [19, 20] and culture-based methods (reviewed in great extension by Vallejo et al [32]). A significant absence in our samples is Serratia , a genus of bacteria that have trypanolytic activity on specific T. cruzi strains [12].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Some differences in the taxonomic composition of triatomine gut bacterial communities were found in our study, in comparison with previous results obtained with non-culture- [19, 20] and culture-based methods (reviewed in great extension by Vallejo et al [32]). A significant absence in our samples is Serratia , a genus of bacteria that have trypanolytic activity on specific T. cruzi strains [12].…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, the ability of some T. cruzi strains to develop in certain vector species depends on the intrinsic qualities of either the parasite or the insect vector, as well as the resident host gut microbiota [18]. Previous studies using non-culturing based methods [19, 20] identified some triatomine gut microbiota characteristics: first, its diversity within each host is low with only one or few genera being dominant; secondly, some bacterial genera appear to be specific to certain triatomine hosts, i.e. Rhodococcus to Rhodnius and Arsenophonus to Triatoma ; finally, lab-reared insects lose part of the original microbiota diversity but conserve most of the bacterial groups found in their wild counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in line with previous studies of other insects (Rani et al, 2009;Belda et al, 2011;Rinke et al, 2011;Gumiel et al, 2015). The potential explanation behind this observation is that insects reared under laboratory conditions are not under the same selective pressure as wild specimens.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have reported a low diversity of bacteria associated with the microbiota of triatomine insects in comparison to other insect groups (Vallejo et al, 2009;da Mota et al, 2012;Gumiel et al, 2015). Our results agree with this observation since we found only 14 different 16S rRNA sequences among all field collecting sites, laboratory specimens, and life stages of the insects.…”
Section: Discussionsupporting
confidence: 91%
“…TcI has also been identifi ed in T. pseudomaculata and R. nasutus in the peridomicile and natural environments of fi ve State of Ceará peri-urban and urban localities (73) . Therein, high TcI and TcII infection rates were detected in peridomestic T. brasiliensis and T. pseudomaculata, respectively (74) . TcI has been most frequently identifi ed in triatomines of the State of Mato Grosso do Sul (75) .…”
Section: Discussionmentioning
confidence: 99%